Caracterização morfométrica de sementes, plântulas e crescimento inicial de cinco espécies arbóreas tropicais - Silva, Elieuda de Castro da (2020)
The development of research pursuing the seedling production of arboreal tropical species is enough relevant for contributing to the adoption of sustainable practices of species manangement, as wel as for the execution of reforesting projects. Thus, in this research Project the objetive was to characterize the morphometric aspects of seeds and seedlings, and of the initial growth, in two differrent environments, of seedlings of the following forest essences: Adansonia digitata L. (“baobá”), Cassia grandis L.f. (“cássia-rosa”), Cedrela odorata L. (“cedro”), Handroanthus serratifolius (Vahl) S.Grose (“ipê-amarelo”) and Tabebuia aurea (Silva Manso) Benth. & Hook.f. ex S.Moore (“craibeira”). The experimental design was developed at the Núcleo de Ensino e Pesquisa em Agricultura Urbana (NEPAU), Departamento de Fitotecnia of the Centro de Ciências Agrárias (CCA), at the Pici Campus of the Universidade Federal do Ceará. For the biometric analysis, a sample containing 100 seeds of each species was used to mensurate the size, width and the thickness. With the generated data were elaborated the histograms, frequency polygonous, boxplot and the descritive statstical calculation. For the morphological analysis of seedlings 100 diaspores of each species were sowed in individual 300 cm3 tubets containing vermiculite and na organic composite in a 2:1 (v/v) volumetric composition. Dayly evaluations and event observations were performed during the germinative proccess, registered by digital fotos and sequentially disposed the throughout the time. The initial growth was analized in two different enviroments: greenhouse and direct sun exposition, during nine periods, in an entirely casualized design, with six repetitions in subdividided parcels where the enviroments constituted the parcels and periods as subparcels. The variable responses were: leaf number, plant height, collet diameter, root size, fresh and dried mass of the aerial parts and roots, and Dickson’s quality index. The seeds presented the folowing dimensions: “baobá” – 10.33 x 8.07 x 6.37 mm; “cássia-rósea” – 16.35 x 12.40 x 4.76 mm; “cedro” – 31.88 x 5.34 x 1.36 mm; “craibeira” – 14.03 x 10.16 x 0.89 mm e “ipê-amarelo” – 10.10 x 6.83 x 0.98 mm. The germination was of phanerocotiledonar epigeal type for “baobá”, “cássia-rósea” and “cedro”, while the “craibeira” and the “ipê-amarelo” presented phanerocotiledonar hipogeal germination. Except for the “cedro” seedlings, all the other studied espécies had the initial growth favored by the direct sun exposition.